206k views
2 votes
2. Consider the following equation x = rh/y Part A: Solve the equation for h.​

2. Consider the following equation x = rh/y Part A: Solve the equation for h.​-example-1
User Noobalert
by
4.7k points

1 Answer

4 votes

Answer:

h = –xy + r

Explanation:

Given the equation,
x = (r-h)/(y):

To solve for h:

Multiply both sides of the equation by y to cancel the fraction on the right-hand side:


x (y) = ((r-h)/(y)) (y)


xy = r - h

Next, subtract r from both sides:

xy – r = r – r – h

xy – r = – h

Next, divide both sides by -1 to solve for h:


(xy - r)/(-1) = (-h)/(-1)

Therefore, the equation for h is:

h = –xy + r

User Ziu
by
5.1k points